Evidence of higher photosynthetic plasticity in the early successional Guazuma ulmifolia Lam. compared to the late successional Hymenaea courbaril L. grown in contrasting light environments - Portes, M. T. [UNESP]; Damineli, D. S. C. [UNESP]; Ribeiro, R.; Monteiro, J. A. F.; Souza, G. M. (Int Inst Ecology, 2010)
The present study investigated changes in photosynthetic characteristics of Guazuma ulmifolia Lam. (early successional species) and Hymenaea courbaril L. (late successional species) grown in contrasting light conditions as a way of assessing photosynthetic plasticity. Early successional species typically inhabit gap environments being exposed to variability in multiple resources, hence it is expected that these species would show higher photosynthetic plasticity than late successional ones. In order to test this hypothesis, light and CO(2) response curves and chlorophyl1 content (Ch1) were measured in plants grown in high and low light environments. G. ulmifolia presented the highest amounts of both Ch1 a and b, especially in the low light, and both species presented higher Ch1 a than b in both light conditions. The Ch1 a/b ratio was higher in high light leaves of both species and greater in G. ulmifolia. Taken together, these results evidence the acclimation potential of both species, reflecting the capacity to modulate light harvesting complexes according to the light environment. However, G. ulmifolia showed evidence of higher photosynthetic plasticity, as indicated by the greater amplitude of variation on photosynthetic characteristics between environments shown by more significant shade adjusted parameters (SAC) and principal component analysis (PCA). Thus, the results obtained were coherent with the hypothesis that the early successional species G. ulmifolia exhibits higher photosynthetic plasticity than the late successional species H. courbaril.
Keywords: leaf gas exchange; light and CO(2) photosynthetic responses; photosynthetic plasticity; plant ecophysiology; tropical forest succession